2021
DOI: 10.3390/life11070638
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Protocols in Early Cancer Detection Based on Liquid Biopsy: A Survey

Abstract: With the advances of liquid biopsy technology, there is increasing evidence that body fluid such as blood, urine, and saliva could harbor the potential biomarkers associated with tumor origin. Traditional correlation analysis methods are no longer sufficient to capture the high-resolution complex relationships between biomarkers and cancer subtype heterogeneity. To address the challenge, researchers proposed machine learning techniques with liquid biopsy data to explore the essence of tumor origin together. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 178 publications
(173 reference statements)
0
19
0
Order By: Relevance
“…Clinical characteristics and radiological reports were reviewed and recorded through an electronic medical system (EMS) [ 20 ], including age at diagnosis, sex, BMI at diagnosis, smoking status, alcohol use status, physical demand (light/heavy), diabetes mellitus, hypertension, cardiovascular disease, hyperlipidemia, and hypothyroidism. The diagnostic criteria for hyperlipidemia were the presence of the diagnosis in the medical record or meeting one or more of the following criteria from the American Association of Clinical Endocrinologists' Guidelines for the Management of Dyslipidemia and Prevention of Atherosclerosis: total cholesterol (TC) ≥6.22 mmol/dL; high-density lipoprotein cholesterol (HDL-C) <1.04 mmol/dL; low-density lipoprotein cholesterol (LDL- C) ≥4.14 mmol/dL; and triglycerides (TG) ≥2.26 mmol/dL.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical characteristics and radiological reports were reviewed and recorded through an electronic medical system (EMS) [ 20 ], including age at diagnosis, sex, BMI at diagnosis, smoking status, alcohol use status, physical demand (light/heavy), diabetes mellitus, hypertension, cardiovascular disease, hyperlipidemia, and hypothyroidism. The diagnostic criteria for hyperlipidemia were the presence of the diagnosis in the medical record or meeting one or more of the following criteria from the American Association of Clinical Endocrinologists' Guidelines for the Management of Dyslipidemia and Prevention of Atherosclerosis: total cholesterol (TC) ≥6.22 mmol/dL; high-density lipoprotein cholesterol (HDL-C) <1.04 mmol/dL; low-density lipoprotein cholesterol (LDL- C) ≥4.14 mmol/dL; and triglycerides (TG) ≥2.26 mmol/dL.…”
Section: Methodsmentioning
confidence: 99%
“… Piccolo et al (2021 )found that KCTD14 was associated with type 2 diabetes in mice and was involved in mediating the regulation of the nutritional environment in the digestive tract. In our study, the prognostic signature constructed by these seven genes can not only guide the prognosis of patients with pancreatic cancer but also provide a reference for the exploration of the immune microenvironment of pancreatic cancer ( Liu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al (297) Liquid biopsies output data are large and complex and therefore, traditional methods fail their efficient process. In this view, ML represents a promising tool for automated analyses of these data and future prediction (307). Different ML algorithms, such as SVM, random forest (RF) and ANNs, have been widely used in the field of medicine (308)(309)(310).…”
Section: Ai In Crc Genomic Data Analysismentioning
confidence: 99%